Burden of genital warts in Ecuador: an observational study in the practice of physicians - Zambrano, Hector; Petrozzi, María Veronica; Aguila, Magdalena Sanchez; Monsanto, Homero Antonio; Cashat, Miguel; Altland, Alexandra; Lindsay, Brianna (Brazilian Journal of Sexually Transmitted Diseases, 2019)
Introduction: Human papillomavirus types 6 and 11 cause 90% of genital warts. Although the epidemiology of cervical cancer and the distribution of human papillomavirus genotypes have been investigated in Ecuador, little is known about the occurrence of genital warts. Objective: To estimate the incidence and prevalence of genital warts among patients routinely presenting at the practice of physicians, describe the demographics of genital warts cases and highlight the physician specialties that treat genital warts, including patterns of consultation and referral in Ecuador. Methods: Participants were a convenience sample of physicians who treat and/or diagnose genital warts in their practices. Physicians completed a daily log, recording the demographics and diagnosis of genital warts in all patients aged 18 to 60 years seen over 10 days in their practices. Physicians then completed a survey recording their practice characteristics and referral patterns of genital warts. Results: A sample of 105 physicians of different specialties participated in the study. Among 12,133 patients, the prevalence of genital warts was 5.5%, and the incidence, 3.7%. Prevalence was 6.9% in men, peaking at 12.6% in those aged from 25 to 29 years old. Prevalence was 5.1% for females, peaking at 6.5% in those aged from 30 to 34 years old. Most women were seen in direct consultations (75%) rather than by referral ones (24%). Most physicians (72%) treated females with genital warts, except for primary care physicians, who referred most cases (88%). Conclusion: Cases of genital warts are frequently encountered by physicians in Ecuador and are typically treated by specialists rather than primary care physicians.